Intervenção fisioterapêutica na qualidade de vida de indivíduos com artrite reumatoide - Spolti, Alexandra (2024)
Rheumatoid arthritis is a disease that causes important musculoskeletal changes and directly impacts the quality of life and functional capacity of individuals who have the diagnosis and live with the disease, which is the focus of this study. Physiotherapy acts on the symptoms that the disease can cause, and can reduce or delay the problems caused by it. In this context, the objective of this dissertation is to verify the effects of a physiotherapeutic intervention program on the quality of life of individuals with rheumatoid arthritis. This is a longitudinal, interventional and association study, initially composed of 12 individuals and completed with 10 individuals diagnosed with Rheumatoid Arthritis, with an average age of 58.50 years and a predominance of females. The instrument used for data collection was developed by a multidisciplinary team. The initial and final assessments involved data collection and application of the specific protocol that assesses quality of life: Medical Outcomes Study 36 - Item Short-Form Health Survey (SF-36), composed of the blocks: Identification; Sociodemographic variables; Health conditions; Self-perceived health; Flexibility and Quality of life. The individuals underwent 15 physiotherapy sessions, through a protocol, twice a week, with an average duration of 50 to 60 minutes at the Physiotherapy Clinic of the University of Passo Fundo, in Passo Fundo/RS. The physiotherapy protocol applied was based on a kinesiotherapy intervention and designed in accordance with previous studies, and is based on mobility, flexibility, muscular strength, balance and gait exercises, which encompass functional movements involving the entire body. The series of repetitions of kinesiotherapy exercises had a gradual progression of series and repetitions during the 15 sessions, according to the individuals' tolerance. With statistically significant results, it was observed that individuals showed an improvement in quality of life after the physiotherapeutic intervention. The physiotherapy program based on a kinesiotherapy intervention protocol proved to be effective in improving the quality of life of individuals living with Rheumatoid Arthritis.